2003
DOI: 10.1002/adfm.200304279
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Blue Emission from Polyfluorene‐Based Light‐Emitting Diodes: Elimination of Fluorenone Defects

Abstract: Polyfluorene (PF)‐based light‐emitting diodes (LEDs) typically exhibit device degradation under operation with the emergence of a strong low‐energy emission band (at ∼ 2.2–2.4 eV). This longer wavelength band converts the desired blue emission to blue–green or even yellow. We have studied both the photoluminescence (PL) and electroluminescence (EL) of PFs with different molecular structures and found that the low‐energy emission band originates from fluorenone defects which are introduced by photo‐oxidization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
259
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 355 publications
(273 citation statements)
references
References 42 publications
9
259
0
5
Order By: Relevance
“…Later, however, it has been shown that emission in the green spectral range originates from a keto defect formed as a result of photooxidation or thermal oxidation [16][17][18][19][20][21][22] . Copolymers and oligomers containing well-defined fractions of fluorenone as a model of the oxidized species showed emission from the fluorenone unit that is photophysically identical to the green band in polyfluorene 23 .…”
mentioning
confidence: 99%
“…Later, however, it has been shown that emission in the green spectral range originates from a keto defect formed as a result of photooxidation or thermal oxidation [16][17][18][19][20][21][22] . Copolymers and oligomers containing well-defined fractions of fluorenone as a model of the oxidized species showed emission from the fluorenone unit that is photophysically identical to the green band in polyfluorene 23 .…”
mentioning
confidence: 99%
“…It is generally accepted that keto defects are generated in PF-type polymers by the oxidation of monoalkylfluorenes (42) and are extremely difficult to eliminate from the monomer feed and, therefore, are incorporated into the polymer. Some research groups give evidence of the formation of 9-fluorenone defects upon chemical, photo-or thermal oxidation (37)(38)(39)43). Considering the UHV atmosphere, however, fluorenone caused by the oxidation process can not be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…In many fluorene-based devices, the development of a structured emission band around 490-500 nm, i.e. at a slightly lower wavelength than the usual green band (500-600 nm), can be observed (43,(46)(47)(48)(49) This emission band has previously been assigned to excimer emission in fresh PFs synthesized by Ni-catalysed Yamamoto coupling (19) and it can be observed also in uncapped PFs prepared by Suzuki coupling (11). The formation of intramolecular excimers with the new C-C bonds formed (38), electric field-induced excimer (48) and fluorenone defects introduced by the cathode (43) also would produce a green emission around 485 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations